Evaluating Tiered Facilitation as a Contextual Learning Approach for CPPOB Adoption in Food MSMEs - Putri Ayu Ogari; Endang Lastinawati; Utan Sahiro Ritonga; Yetty Oktarina; Rita Novia Sari; Mukhlis (Jurnal Penelitian Pendidikan IPA, 2026)
Ensuring compliance with Good Processed Food Production Practices (CPPOB) is a critical challenge for food MSMEs. This study evaluates a structured, tiered facilitation model—comprising socialization, technical guidance, and monitoring—to improve CPPOB adoption in Palembang. Using a quantitative pre–post intervention design, data were collected from 40 participants (owners and employees) via a validated Likert-scale instrument. The Wilcoxon Signed Rank Test revealed a significant increase in CPPOB implementation post-intervention, with Z = −5.553 and p = 0.000. Results showed no negative ranks, indicating uniform behavioral and operational improvement. The evaluation phase emerged as the most decisive factor, highlighting the importance of iterative feedback in internalizing food safety protocols. These findings provide empirical evidence on facilitation as a catalyst for organizational discipline. This study contributes to applied science by offering a scalable framework for food safety literacy, bridging the gap between theoretical hygiene standards and practical implementation in resource-constrained MSME clusters.